The role of reciprocal actions of giving and receiving support on eudaimonic workplace well-being - Febrina, Sartika Ria; Salendu, Alice (Empathy : Jurnal Fakultas Psikologi, 2023)
Employee well-being is gaining increasing attention from various quarters. Studies related to the relationship between reciprocal actions of social support and individual well-being tend to be conducted separately. Additionally, the relationship between receiving support from colleagues and employee well-being also tends to show relatively low to moderate associations. Therefore, this research aims to examine the role of the dynamic reciprocity of social actions in well-being, through an investigation of the mediating role of organization citizenship behavior toward individuals (OCB-I) in the relationship between perceived co-worker support (PCS) and eudaimonic workplace well-being (EWWB). The research participants were active workers who had been working for a minimum of 1 year in their current organization, gathered through convenience sampling techniques. Mediation analysis results indicate that OCB-I significantly mediates the relationship between PCS and EWWB, thus supporting the hypothesis of this research. This study demonstrates the role of social interaction, particularly the dynamics of support among employees, in relation to employee well-being.